Pelatihan Pembukuan Sederhana Untuk Paguyuban Kuliner Laksa Tangerang - Metta Susanti; Selfiyan Selfiyan; Aldi Samara; Jenni Jenni; Sutandi Sutandi; Peng Wi; Yunia Oktarini (Svarga Pena : Jurnal Pengabdian Kepada Masyarakat, 2024)
Our team carries out community service for the Laksa Tangerang Culinary Association. The Tangerang Laksa Culinary Association is an association of Laksa Culinary MSME’s / laksa traders who sell in Tangerang. The Laksa culinary community is located at Jl. Mochammad Yamin No.113, RT.001/RW.004, Babakan, Kec. Tangerang, Tangerang City, Banten 15118.The aim of the Community Service Implementation (PKM) activity in simple bookkeeping training for the Laksa Tangerang Culinary Association is so that MSME’s are able to make their own bookkeeping so that they are systematic and orderly in carrying out financial records so that income, expenses and profits can be measured and know the development of their business.The method for implementing community service for the Laksa Tangerang Culinary Association is divided into three stages, namely the initial survey stage (interviews and field observations), the second stage is the implementation of training, and the final stage is the preparation of the final report and publication. The results obtained from this activity are that you can increase your knowledge and skills in running your business through simple bookkeeping/recording that is easy to apply, thereby increasing your motivation to work.Based on surveys conducted in the field, it was shown that the high level of business activities carried out by business actors was not accompanied by an understanding of the supporting factors in carrying out business activities such as simple bookkeeping so that business actors only focused on profits without paying attention to the supporting factors of the business. Based on this, MSME entrepreneurs need an understanding of simple bookkeeping to support business activities so that they can develop well in the future.